Coping with Drought among the Communities Living in the Lake Victoria Basin of Kenya - Chumo, J. K. (Journal of Social and Development Sciences, 2012)
Drought is of great concern throughout the continent of Africa because of its devastating effects that it has inflicted on the economy of some of the countries. Drought has been recorded to be one of the most felt disasters in recent years in Kenya. The drought that affected Kenya in the year 2000 and 2010 was indeed remarkable in that the country resorted to loss of lives, loss of livestock, power rationing and drying of agricultural crops among other problems. This study developed a technique to depict spatially, the extent, relative severity and location of areas mostly affected by drought in the Lake Victoria basin of Kenya. This was done using the normalized difference vegetation index (NDVI) plots and maps developed using the Geographical Information System (GIS) software. The indices were generated using the C++ program. NDVI indices revealed that most parts of the basin were moderately dry throughout the year. The study investigated the impacts of drought in the area by use of questionnaires and interviews. The impacts identified were mainly crop failure, depletion of water resources and lack of pasture for livestock. The complex and multidimensional nature of drought requires a long term, well-organized and coordinated research plan and action involving all the stakeholders. This study summarized coping strategies adopted by the communities living within the Lake Victoria basin to mitigate drought phenomenon. Some of the strategies include; planting of drought resistant crops, food storage sharing and purchasing of food among others. Recommendations have been suggested for policy makers, planners and agriculturalists to implement to improve agricultural output in a drought prone area like the Lake Victoria Basin of Kenya. In particular, the study highly recommends development of a comprehensive drought policy to be implemented in managing drought in Kenya.